Pengaruh Karakteristik Anggota Komunitas Berkebun Semarang Terhadap Keputusan Melakukan Urban Farming di Kota Semarang, Jawa Tengah - Christine, Hosianna; Gayatri, Siwi; Mariyono, Joko (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Urban farming refers to agricultural practices conducted in urban areas, offering a wide range of benefits. The success of the Komunitas Berkebun Semarang as a platform for the residents of Semarang to learn about and implement urban farming practices is closely related to the individual characteristics of its members. This study aims to examine the influence of member characteristics such as age, educational background, training participation, family acceptance, and number of family members on the decision to engage in urban farming. The research was conducted from February to March 2025 in Semarang City. The research location was selected purposively, based on the consideration that the Komunitas Berkebun Semarang is one of the most active urban farming communities in the city. The sampling technique employed was probability sampling, specifically simple random sampling. The sample size was determined using the Slovin formula, resulting in a total of 70 respondents. Data collection was carried out through interviews using structured questionnaires and field observations. The data were analyzed using descriptive statistics and binary logistic regression analysis. The results of the binary logistic regression test indicate that age, educational background, training participation, family acceptance, and number of family members simultaneously have a statistically significant influence on the decision to engage in urban farming. However, partially, only educational background, training participation, and family acceptance were found to have a significant influence, while age and number of family members did not show a significant effect.